Evaluating factors influencing youth participation in agricultural enterprises: Implications for food security and agribusiness - Ongama Giwu; Lelethu Mdoda; Samuel S. Ntlanga; Olwethu Loki (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Agriculture is crucial for economic growth, yet youth engagement in agricultural enterprises is declining due to concerns related to perceived profitability, resource access, and social stigmas. Understanding these determinants is vital for fostering youth interest in agriculture and promoting sustainable rural development and food security.